In vitro assessment of internal implant-abutment connections with different cone angles under static loading using synchrotron-based radiation - Johannes Angermair; Gerhard Iglhaut; Konrad Meyenberg; Wolfram Wiest; Alexander Rack; Simon Zabler; Tobias Fretwurst; Katja Nelson; Florian Kernen (BMC, 2024)
Abstract Background The stability of implant-abutment connection is crucial to minimize mechanical and biological complications. Therefore, an assessment of the microgap behavior and abutment displacement in different implant-abutment designs was performed. Methods Four implant systems were tested, three with a conical implant-abutment connection based on friction fit and a cone angle < 12 ° (Medentika, Medentis, NobelActive) and a system with an angulated connection (< 40°) (Semados). In different static loading conditions (30 N − 90º, 100 N − 90º, 200 N − 30º) the microgap and abutment displacement was evaluated using synchrotron-based microtomography and phase-contrast radioscopy with numerical forward simulation of the optical Fresnel propagation yielding an accuracy down to 0.1 μm. Results Microgaps were present in all implant systems prior to loading (0.15-9 μm). Values increased with mounting force and angle up to 40.5 μm at an off axis loading of 100 N in a 90° angle. Conclusions In contrast to the implant-abutment connection with a large cone angle (45°), the conical connections based on a friction fit (small cone angles with < 12°) demonstrated an abutment displacement which resulted in a deformation of the outer implant wall. The design of the implant-abutment connection seems to be crucial for the force distribution on the implant wall which might influence peri-implant bone stability.